An Unusual Cause of Necrotising Fasciitis in a Young Male with Juvenile Dermatomyositis - Adelaide Ankomaa Asante; Josephine Nsaful; Dzifa Dey (Case Reports in Rheumatology)
Juvenile dermatomyositis (JDM) is a rare condition worldwide, affecting children younger than 16 years. It is characterized by weakness in the proximal skeletal muscles and a pathognomonic skin rash. Patients with JDM develop complications that are usually a consequence of vasculopathy affecting multiple organ systems. Occult gastrointestinal (GI) perforation is an uncommon complication and is associated with an increased risk of mortality due to a delay in diagnosis. We report on a 14-year-old male with JDM with an aggressive course over two years and severe clinical manifestations. The patient developed necrotizing fasciitis, an unusual rapidly progressing lethal infection of the fascia resulting from bowel contents seeping from multiple intestinal perforations. This case, less commonly seen in males, highlights the occurrence of multiple phenomena—JDM complicated by skin and gastrointestinal vasculopathy with resultant development of multiple GI perforations and consequently life-threatening necrotizing fasciitis of the leg. Physicians need a high index of suspecting GI perforation in JDM patients as the delayed recognition of this complication can result in significant morbidity and/or mortality since the typical symptoms of perforation may be absent.